A Multi-Disciplinary Review of Time-Driven Activity-Based Costing: Practical Considerations for Spine Surgery. Issue 3 (April 2023) - Ali, Daniyal Mansoor; Leibold, Adam; Harrop, James; Sharan, Ashwini; Vaccaro, Alexander R.; Sivaganesan, Ahilan
Study Design: A multi-disciplinary review. Objectives: To provide a roadmap for implementing time-driven activity-based costing (TDABC) for spine surgery. This is achieved by organizing and scrutinizing publications in the spine, neurosurgical, and orthopedic literature which utilize TDABC and related methodologies. Methods: PubMed and Google Scholar were searched for relevant articles. The articles were selected by two independent researchers. After article selection, data was extracted and summarized into research domains. Preferred reporting items for systematic reviews and meta-analyses (PRISMA) systematic review process was followed. Results: Of the 524 articles screened, thirty-five articles met the inclusion criteria. Each included article was examined and reviewed to define the primary research question and objective. Comparing different procedures was the most common primary objective. Direct observation along with one other strategy (surveys, interviews, surgical database, or EMR) was most commonly employed during process map development. Across all surgical subspecialties (spine, neurologic, and orthopedic surgery), costs were divided into direct cost, indirect cost, cost to patient, and total costs. The most commonly calculated direct costs included personnel and supply costs. Facility costs, hospital overhead costs, and utilities were the most commonly calculated indirect costs. Transportation costs and parental lost wages were considered when calculating cost to patient. The total cost was a sum of direct costs, indirect costs, and costs to the patient. Conclusion: TDABC provides a common platform to accurately estimate costs of care delivery. Institutions embarking on TDABC for spine surgery should consider the breadth of methodologies highlighted in this review to determine which type of calculations are appropriate for their practice.